The geoecological analysis of Lake Tuchne (Volyn Polissia) and assessment of sapropel reserves in it. - Martyniuk, Vitalii O.; Kovalchuk, Ivan P.; Zubkovych, Ivan V.; Pavlovska, Tetiana С.; Sukhodolska, Iryna L. (My University, 2024)
The administrative-territorial reform in Ukraine, which began in 2015, opened up prospects for newly created territorial communities to determine the resource potential of local territories under control and develop strategies for balanced nature use and their progressive development. The lakes, which have a significant potential for sapropel resources, take an important place in the Polissia region of Ukraine. Given the above, there is a need for a comprehensive study of specific lakes and justification of recommendations for the rational use and protection of their water and sapropel resources. The object of our research is Lake Tuchne, Volyn Polissia. The catchment area of Lake Tuchne is 10.05 km2 , and the reservoir itself is 0.39 km2 . A bathymetric model of the lake was built with a depth interval of 0.5 m. The vegetation index (NDVI) for the reservoir over the past five years has been varying from -0.53 (12/02/2021) to +0.48 (07/15/2021). The research presents a stratigraphic section of the reservoir sediments. The area of accumulated sapropel is 20.5 hectares, the average thickness is 4.46 m, and the maximum is 10.0 m. The ash content of sapropel varies within 17.5-37.5% (on dry substance). The content of Fe2 O3 in the core ranges from 2.53% to 7.26%. The distribution of CaO compounds in the samples ranges from 2.09 to 8.12%. The CO2 content varies from 1.97 to 9.72%. The concentration of Р2 О5 in sapropel samples is 0.19-0.53%. The distribution of S in sapropel deposits ranges from 0.23 to 1.09%. The pH (salt extract) distribution in the core samples varies from moderately alkaline (7.63) to close to neutral – 5.97. A digital landscape map of the lake was construct ed with the selection of the littoral and sublittoral-profundal aqua sub-areas and five types of aquafacies. A landscape-metric analysis of the natural and aquatic complex of the lake was carried out. The potential of water resources of Tuchne lake is 827.0 thousand m3 . Sapropel reserves of category A are 914,000 m3 , and based on a conditional 60.0% humidity, they are 155,000 tons. The species com position of sapropel is represented by zoogenic, organo-ferrous, and organo-limestone species. The total stock of sapropel in the lake basin is 52.5% of its volume. The reservoir is promising for extracting sapropel due to its quality characteristics and hydro-technical prerequisites for operation. Mined sapropel can be used in agriculture, medicine, recreation, etc. Implementing this task will improve the geoecological state of the lake and the quality of its water resources.
Keywords: geoecological analysis; lake; bathymetry; landscape map; complex water basin; sapropel